Strategi Pembentukan Karakter Siswa Berbasis Nilai Agama dan Budaya di Era Digital Pada Jenjang Sekolah Menengah Pertama - Syaiful Alim (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The rapid development of digital technology has significantly influenced students’ behavior and character, requiring adaptive character education strategies without neglecting religious and cultural values. This study aims to analyze strategies for developing students’ character based on religious and cultural values in the digital era at the junior secondary school level. This research employed a qualitative approach using a case study method conducted at SMP Negeri 1 Kandangan. Data were collected through in-depth interviews, observations, and documentation involving the school principal, Islamic Religious Education teachers, subject teachers, and students. The findings indicate that character development strategies are implemented in an integrated manner through school culture habituation, religious activities, teacher role modeling, wise use of digital technology, and the support of extracurricular activities. Religious and cultural values are continuously internalized to foster students’ religious character, discipline, responsibility, and social awareness. However, several challenges were identified, including low digital literacy, negative influences of social media, and limited parental supervision. This study concludes that character education based on religious and cultural values remains relevant and effective in the digital era when supported by strong school commitment, exemplary teachers, and synergy between schools and parents.